2019
DOI: 10.18699/vj19.492
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C in fleshy fruits: biosynthesis, recycling, genes, and enzymes

Abstract: L-ascorbic acid (vitamin C) is a plant secondary metabolite that has a variety of functions both in plant tissues and in the human body. Plants are the main source of vitamin C in human nutrition, especially citrus, rose hip, tomato, strawberry, pepper, papaya, kiwi, and currant fruits. However, in spite of the biological significance of L-ascorbic acid, the pathways of its biosynthesis in plants were fully understood only in 2007 by the example of a model plant Arabidopsis thaliana. In the present review, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 82 publications
(127 reference statements)
1
5
0
Order By: Relevance
“…In citrus fruits, three oxocarboxylic acids, i.e. citric, malic, and acetic have the greatest effect on the fruit taste [6,7,15]. The sweetness is determined by low-molecular carbohydrates, i.e.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In citrus fruits, three oxocarboxylic acids, i.e. citric, malic, and acetic have the greatest effect on the fruit taste [6,7,15]. The sweetness is determined by low-molecular carbohydrates, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, these compounds make a different contribution to the creation of a feeling of sweetness. If we take the sweetness of sucrose to be 100%, then the sweetness of glucose is 74%, and the sweetness of fructose is 173% [15,16]. Thus, taking into account the content of basic acids and sugars in citrus fruits, it makes it possible to determine the effect of drugs on the main taste properties after treating plants with insecticides.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have indicated that many plants differ in their pathways to synthesize AsA, and may switch pathways during fruit ripening (Badejo et al, 2012;Liao et al, 2021). In an extensive review, Tyapkina et al (2019) conclude that there is no unequivocal evidence for the existence of a predominant pathway of AsA biosynthesis in fleshy fruits. In pepper plants, the L-galactose pathway has been studied by several researchers (Aloś et al, 2013;Goḿez-Garcıá and Ochoa-Alejo, 2016;Rodrıǵuez-Ruiza et al, 2017), but there is very limited understanding about the other AsA biosynthesis pathways.…”
Section: Introductionmentioning
confidence: 95%
“…ROS are known to increase with ripening due to increased respiration, which results in increased antioxidant activity resulting from higher AsA and phenolic compounds [47]. In tomato there is a significant increase in AsA synthesis, recycling, and degradation during ripening [48]. It has been suggested that phenolic compounds are involved in the stability of AsA, as both AsA and total phenolic content in pink stage fruit stored at 12 • C increased during a 15-d storage period [47].…”
Section: Introductionmentioning
confidence: 99%